Recording Toponyms to Document the Endangered Hopi Language. Issue 2 (4th April 2014) - Hedquist, Saul L.; Koyiyumptewa, Stewart B.; Whiteley, Peter M.; Kuwanwisiwma, Leigh J.; Hill, Kenneth C.; Ferguson, T. J.
ABSTRACT The toponyms of Hopitutskwa ("Hopi land") explicate Hopi history and culture. Place‐names mark sacred locations, landforms associated with deities and historical events, springs, trails, and "footprints" of ancestral villages, petroglyphs, and other archaeological sites. The National Science Foundation funded a collaborative project to document the Hopi language by recording toponyms and associated narratives. Interviews with 15 Hopi individuals produced linguistic and ethnocartographic records of 282 place‐names. Audio and video recordings preserve the vocalization of place‐names pronounced in Hopi as well as their use in a larger Hopi language contextualization. The variety and distribution of toponyms discussed during interviews demonstrates how Hopis remember, interact with, and honor their land.